Fungal endophytes in the needles of native and exotic pine species in a planta-tion in Northwestern Türkiye - Asko Tapio Lehtijarvi; Ayse Gülden Aday Kaya; Tuğba Doğmuş Lehtijarvi (Turkish Journal of Forestry, 2023)
The endophytic fungi present in needles of Pinus sylvestris, Pinus pinaster, Pinus nigra, Pinus taeda and Pinus radiata were investigated in Kerpe Research Forest, İzmit in 2016. Ten trees of each pine species were sampled systematically. Previous years green needles were sampled from the lower part of the canopy, from two equally spaced positions around the tree. Each needle was surface sterilized and cut into 0.5 cm sections then individually placed onto malt extract agar plates. DNA was ex-tracted from reprensentative seven isolates and amplified using primers ITS1 and ITS4 targeting the nuclear 5.8S rDNA gene and the two ITS regions flanked between 18S and 28S rDNA genes. Amplicons sequenced in both directions using the univer-sal fungal primers ITS1 and ITS4. Isolations from a total of 1000 needles (200 from each pine species) yielded 750 fungal isolates. Pestalotiopsis funerea (Desm.) Steyaert was isolated at the highest frequency followed by Acremonium sp., Cladio-sporum sp. and Cyclaneusma minus.